Effect of anticonvulsive treatment on neuropsychological performance in children with BECTS - Tacke, Moritz; Reuner, Gitta (European journal of paediatric neurology, 2016)
Introduction Benign epilepsy with centrotemporal spikes (BECTS) is a common epilepsy syndrome in childhood. Besides the occurrence of seizures, mild cognitive impairments and behavioral problems affecting language skills, spatial perception, memory, executive function, and academic achievement might be present. There is no international consensus about the decision whether or not to treat affected children. The influence of treatment on cognitive functions is debated. Methods Patients diagnosed with BECTS were assessed in short term auditory memory, long-term verbal memory, intelligence and behavior using the “number recall” test from the Kaufman assessment battery for children, the “verbal learning memory test”, the “culture free intelligence test” and the “child behavior checklist” prior to a randomized controlled antiepileptic therapy and after a treatment period of 6 months with either sulthiame or levetiracetam. Results 43 of 44 randomized patients were analyzed. One patient had to be excluded due to protocol violation. Patients who completed the study showed a non-significant improvement in parent-reported behavioral problems under therapy. Cognitive skills were not affected. Conclusion The present data suggest that antiepileptic drug treatment of children with BECTS with either sulthiame or levetiracetam does not affect cognitive performance. Behavior improved in a subset of patients though not reaching statistical significance.